DESIGNING THE ASSESSMENT FOR A COMPETENCE - BASED CURRICULUM. A CONCEPTUAL FRAMEWORK - Daniel ANDRONACHE (Studia Universitatis Babes-Bolyai, 2016)
The article presents a synthesis and an analysis of the literature aiming to create conceptual framework for the assessment of the competence based-curriculum. Contemporary orientations in education promote the necessity and the importance of the competences development through an adequate curriculum design. In this context the curriculum assessment becomes extremely important because its role is to provide information about the effectiveness and functionality of the education process and of the education system, as a whole, in order to improve it. In this study we aim to define and describe the processuality implied by the assessment of a competence-based curriculum, analysing the levels and the stages that are involved. ZUSAMMENFASUNG. Der Artikel stellt eine Zusammenfassung und eine Literaturanalyse vor und zielt einen begrifflichen Rahmen zu schaffen, der relevant für die Beurteilung des Kompetenzen-zentriet Curriculums ist. Die zeitgenössische Leitlinien in Bildung fördern die Notwendigkeit und die Bedeutung der Ausbildung den Kompetenzen bei Schülern durch eine geeignete Gestaltung des Curriculums. In diesem Kontext wird die curriculare Beurteilung extrem wichtig, weil ihre Rolle Informationen über die Effektivität und Funktionalität des Bildungsprozesses und des Bildungssystems als Ganzes im Hinblick auf seiner Verbesserung anzubieten ist. In dieser Studie haben wir vor die Prozessualität der Beurteilung des Kompetenzen-zentriet Curriculums zu definieren und zu konturieren. Wir analysieren auch die Ebenen und die Stufen, die dieses Curriculum betrifft. Schlüsselwörter: Kompetenz, Curriculumgestaltung, Bewertung